Elimination of Dengue Virus with Antiviral Compound and Appropriate Technology - Farihah, Neni Isna; Wijayanti, Alvia Rachma; Sucipto, Teguh Hari; Putri, Deva Permata; Ihsan, Anaqi Syaddad; Fauziyah, Shifa; Saputri, Ratih Dewi; Damayanti, Mamik (Universitas Airlangga, 2023)
Infection with the dengue virus by the Aedes aegypti mosquito vector is in the form of dengue hemorrhagic fever (DHF), which can cause a decrease in platelets and even death. The parasitic drug niclosamide, which is effective against dengue virus serotype 2 (DENV-2) is used to prevent further dengue virus infection. Many tests were carried out using inhibitors such as doxorubicin (SA-17), glycoside inhibitors in the form of deocynojirimycin (DNJ) and castanospermine (CSP), carbohydrate-binding agents (CBA), and the use of heparan sulfate aimed at inhibition of the adsorption process and replication process, as well as improper protein folding to prevent the conformation of virus merger. The elimination process can also be carried out using antiviral compounds found in the leaves of Psidium guajava and Carica papaya, which have inhibitory activities of 92.6% and 89.5%, respectively; propyl gallate, with a percent inhibition of dengue virus envelope protein serotype 2 of 53-9.85%; isobutyl gallate, with CC50 values of 167.19 g/mL and an inhibitory value (IC50) of 4.45; Cissampelos Pariera Linn methanol extract, with progressive inhibition as the Cipa extract concentration increased with an IC50 value of 6.1μg/ml Preventive methods are also carried out in several ways, namely by utilizing hydrophobic liquid in the form of silicone oil (low-viscosity polydimethylsiloxane, or L-PDMS), the use of eave tubes in home tubes inserted with insecticides, and utilizing ultrasound with a frequency of 100 kHz and 90 dB to repel mosquitoes carrying dengue virus vectors.